2020
DOI: 10.1016/j.amsu.2020.10.018
|View full text |Cite
|
Sign up to set email alerts
|

FAST accuracy in major pelvic fractures for decision-making of abdominal exploration: Systematic review and meta-analysis

Abstract: Background Major pelvic fractures are often associated with intra-abdominal organ injuries. Considering patients’ hemodynamic status, Focused Assessment with Sonography for Trauma (FAST) can facilitate decision-making for abdominal exploration. Non-therapeutic exploratory laparotomy from pelvic fractures should be avoided. Aim of this study is to determine the accuracy of FAST in diagnosing significant intraabdominal hemorrhage that leads to determine whether or not to pursue therapeutic abdominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It defined significant intraabdominal injury as an injury necessitating surgical intervention through abdominal exploration. The study concluded that the FAST accurately identified significant intraabdominal hemorrhage in patients with pelvic fractures [ 24 ]. Consequently, we concur with the authors that, in this patient population, the evaluation of the FAST should not focus on its ability to detect any free fluid, as a positive FAST is defined in accordance with the ATLS guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…It defined significant intraabdominal injury as an injury necessitating surgical intervention through abdominal exploration. The study concluded that the FAST accurately identified significant intraabdominal hemorrhage in patients with pelvic fractures [ 24 ]. Consequently, we concur with the authors that, in this patient population, the evaluation of the FAST should not focus on its ability to detect any free fluid, as a positive FAST is defined in accordance with the ATLS guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The same follows for renal lesions and pelvic fractures, although intraperitoneal fluid can be detected in cases where there is clinically significant extraperitoneal bleeding. [ 7 , 25 ] Once FAST/e-FAST protocol is not intended to detect extraperitoneal bleeding, strictly speaking, isolated extraperitoneal injuries are not supposed to be considered false negatives per se ; however, it is important to remember this possibility. Clinical information such as hematuria and pelvic instability at physical examination should be taken into account to pursue further investigation in these scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of pelvic trauma, e-FAST has a low sensitivity in the evaluation of possible retroperitoneal hemorrhage [ 30 , 31 ]. However, it helps to determine potential symphyseal diastasis, showing a high correlation with computed tomography (CT) measurements [ 32 , 33 ].…”
Section: Imaging Evaluationmentioning
confidence: 99%